Strategi Pengasuh Asrama Dalam Pembinaan Akhlak Santri di Pondok Pesantren Nurul Yaqin Siti Manggopoh Kecamatan Lubuk Basung Kabupaten Agam - Nesa Alia Putri; Supriadi Supriadi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to describe the strategies of dormitory caregivers in fostering the morals of students at the Nurul Yaqin Siti Manggopoh Islamic Boarding School, Lubuk Basung District, Agam Regency. Through this type of research that uses a qualitative descriptive approach that explains the strategy of dormitory caregivers in fostering the morals of students at Pondok Pesantren Nurul Yaqin Siti Manggopoh Kecematan Lubuk Basung, Agam Regency. and observation for supporting data from interview results. The results of the study show that the dormitory caretakers at the Nurul Yaqin Siti Manggopoh Islamic Boarding School have many strategies that have been tried in fostering the morals of students, namely firstly the dormitory caretakers will give sanctions to students who steal, and will follow up for students who do not want to admit it, secondly reprimand and giving punishment to students who speak harshly. With the existence of several strategies that have been implemented by the dormitory caregivers, it is concluded that the caregivers of the Islamic Boarding School Nurul Yaqin Siti Manggopoh apply several strategies in fostering the morals of students, where through these strategies it is hoped that dormitory caregivers can foster the morals of the students to become more virtuous, civilized, and have noble character.